Quantitative Study on Morphological Characteristics of Barchan Dunes in Yamarak Desert, China - Guang-Pu, Jia; Guang, Yang; Xue-Ying, Han; He-Jun, Zuo; Yun-Feng, Yao (Frontiers in Earth Science, 2022)
Although scholars have conducted many studies on barchan dunes in deserts and sandy areas around the world, few studies have been conducted on the morphological characteristics and changes in movement patterns of barchan dunes in the Yamarak Desert, China. To assess the changes in and movement patterns of these dunes, As well as the impact on the wind-sand hazards and geohazards around the study area, we selected several typical barchan dunes of different sizes in the Yamarak Desert and measured and calculated their morphologies using a combination of a 3-D laser scanner (RIEGL VZ-2000) and remote sensing image interpretation. The results show that the average coverage of the barchan dunes in the Yamarak Desert was 37.19%. Moreover, 62.81% of this area was covered by interdune sites. The movement velocity of the barchan dunes in this study area was 0–20 m/a, with an average movement velocity of 8.45 m/a. Of these dunes, 44.18% were fast-dominated dunes, 37.20% were particularly fast-dominated dunes, and 18.62% were moderately fast-dominated dunes. The barchan dunes moved in the 95–130° direction, which was basically consistent with the main wind direction of the area. The determination and function fitting of the barchan dune morphology shows that the correlation coefficients between all of the morphological parameters are greater than 0.8, except for the degree of spread and the symmetry of the two wings. We suggest adding the influences of other factors affecting barchan dunes and dune chains in the Yamarak Desert in future studies and paying attention to new wind-sand hazards and geohazards in the downwind corridor.